Strengthening the Professionalism of Pre-Service Elementary School Teachers in the Preparation of Learning Tools on the Independent Curriculum - Kartono, Kartono; Pranata, Rio; Hairida, Hairida; Halidjah, Siti; Hartoyo, Agung; Kresnadi, Hery; Salimi, Asmayani; Ghasya, Dyoty Auliya Vilda (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this community service activity is to increase the knowledge and understanding of prospective elementary school teachers in preparing learning tools based on the Independent Curriculum and to determine the participants’ response to the training activities carried out. The method used is training and hands-on practice. With the stages of activity consisting of the preparation stage, activity implementation stage, and activity evaluation. The instruments used were a preliminary study questionnaire and a training participant response questionnaire. Training activities were carried out at the Shanti Bhuana Institute, Bengkayang Regency with a total of 70 prospective elementary school teachers. The results of the training showed that 67.2% of participants felt very helpful and 32.8% answered helpful, indicating that this training was declared useful for prospective elementary school teachers and motivated prospective teachers to develop their own learning tools so as to improve the quality of education in Bengkayang Regency.